2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.23720
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Online Versus Paper Spatial Testing Methods

Abstract: Norma Veurink is a Senior Lecturer in the Engineering Fundamentals Department at Michigan Technological University where she teaches introductory engineering courses and a spatial visualization course designed for engineering students with poorly developed spatial visualization skills. Ms. Veurink manages several summer programs that introduce middle and high school students to engineering. She is active in the Engineering Design Graphics Division of ASEE. Comparison of On-line versus Paper Spatial Testing Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Some authors have contrasted the electronic and paper formats for administering this assessment. In [18] authors found that freshmen taking the test through an LMS scored on average a full point lower than those taking a paper version of the test, even though the LMS group had higher Math ACT averages than the paper groups. They also mentioned that some students may score lower because in the electronic version it is not possible to make marks.…”
Section: Face-to-face (Ftf) Trainingmentioning
confidence: 98%
“…Some authors have contrasted the electronic and paper formats for administering this assessment. In [18] authors found that freshmen taking the test through an LMS scored on average a full point lower than those taking a paper version of the test, even though the LMS group had higher Math ACT averages than the paper groups. They also mentioned that some students may score lower because in the electronic version it is not possible to make marks.…”
Section: Face-to-face (Ftf) Trainingmentioning
confidence: 98%
“…Strong SVS have been shown to be critical to the success of engineers and students in the fields of Engineering, Technology, Computer Science, Chemistry, Computer Aided Design and Mathematics 3,17,18,19 . The assessment and remediation of those skills is growing in engineering curricula across the country 2,17,18,20,21 . The 3D spatial skills of female often lag behind those of men 17 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because of the opportunity for a more datarich assessment, prior work had developed an online version of the PSVT:R [6]. It is necessary to complete separate assessments of paper-based and computer-based tests, even if they are otherwise identical, as instruments show marked difference in their results when given via different platforms [13].…”
Section: Introductionmentioning
confidence: 99%